Physical Activity Enforces Well-being or Shame in Children and Adolescents With Asthma: A Meta-ethnography - Thomas Westergren PhD; Hanne Aagaard PhD; Elisabeth O.C. Hall PhD; Mette Spliid Ludvigsen PhD; Liv Fegran PhD; Nastasja Robstad PhD; Åsa Audulv PhD (SAGE Publishing, 2024)
Asthma symptoms and experiences of dyspnea challenge participation in physical activity (PA). Therefore, in-depth understanding of experiences with PA is essential. In this meta-ethnography, we synthesized published qualitative studies of experiences of children and adolescents with asthma that influenced, or limited, participation in PA. We followed Noblit and Hare's 7 phases of meta-ethnography. We searched relevant databases by December 18, 2023 for published peer-reviewed studies (Medline (OVID), Embase (OVID), PsycINFO (OVID), CINAHL (EBSCHOhost), SPORTDiscus (EBSCHOhost), SocINDEX (EBSCHOhost), and Social Science Citation Index (WoS)) and theses (ProQuest Nursing & Allied Health Source, ProQuest Healthcare Administration Database, and ProQuest Public Health Database). We conducted study selection and assessment of methodological quality and data extraction using Joanna Briggs Institute's methodology. Sixteen reciprocally related qualitative studies, representing experiences of 238 children and adolescents aged 4 to 18 years were included. We translated primary study concepts and findings into 3 themes covering relationships with others, emotions, and behaviors related to PA participation: (1) feeling related to and connected with friends and family in PA; (2) acquiring and managing new PA and asthma skills; and (3) enjoying PA and experiencing well-being. We also defined 3 themes covering aspects related to PA limitations: (4) feeling misunderstood and penalized in relation to PA; (5) experiencing nervousness, embarrassment, shame, and sadness during PA; and (6) withdrawing from PA due to asthma, environment, and/or socially imposed attitudes. The themes were synthesized into the following lines of argument: children and adolescents with asthma experience that PA enforces empathic/non-empathic relationships, vulnerability, and awareness; PA enhances resilient participation and well-being, or reinforces resignment to isolation and shame. From the outset of either relatedness or being penalized, youngsters with asthma either manage well and experience well-being, or experience shame and withdrawal. Registration: PROSPERO No. 164797